Answer:
the ordered pairs should be y and x
Step-by-step explanation:
Answer:
C.
Step-by-step explanation:
(f+g)(x) ➡ f(x) + g(x)
x/2 - 2 + 2x^2 + x - 3 = 2x^2 + 3x/2 -5
Answer:
6: 12
7: 14
8: 16
Step-by-step explanation:
You do the last (y) term given [18] minus the first (y) term [10] given divided by how many terms it takes to get from the last (y) term given minus the first (y) term given [4]. So the equation looks like this:
(18 - 10)/4= 8/4 = 2
X = 4 ; x = 3 + i ; x = 3 - i
(If you get a zero that is adding or subtracting, you always need to write it twice but change the sign do they cancel out)
f(x) = (x-4)(x-3-i)(x-3+i)
Distributing the last two parenthesis first is always the best way to start off
(x-3-i)(x-3+i) has (x-3) in common so it can be separated to
(x-3)^2 + (-i)(+i)
(x^2 - 6x + 9) ; (-i)(+i) is always +1
(x^2 - 6x + 9) + 1
(x^2 - 6x + 10)
Now multiply this with (x-4)
x^3 - 6x^2 + 10x
- 4x^2 + 24x - 40
x^3 - 10x^2 + 34x - 40 = f(x)
Answer:
2.25 gallons
Step-by-step explanation:
ggggdhdhdhdhdjd its right